Phase diagram and scattering intensity of binary amphiphilic systems - Gompper, Gerhard; Schwarz, Ulrich S. (Zeitschrift für Physik. B, Condensed matter, 1995)
A Ginzburg-Landau model with a scalar and a vector order parameter, which describe the concentration and orientation of the amphiphile, respectively, is used to study the phase diagram and the scattering intensity of binary amphiphilic systems. With increasing amphiphile concentration, the calculated phase diagram shows the typical sequence of ordered phases observed experimentally, that is micellar liquid → cubic micellar → hexagonal → lamellar → cubic bicontinuous → invers hexagonal. The scattering intensity in the homogeneous phase is calculated in the oneloop approximation. In the vicinity of a phase transition to an ordered phase, the intensity is found to show a 1/q behavior for not too small wave vectorsq, followed by a small peak, and a 1/q2 decay for large wave vectors, in agreement with experimental observations in theL3-(or sponge-)phase.